Demonstration of ameliorative effect of lacosamide: in a rat model of sepsis-induced critical illness polyneuropathy. (September 2015) - Solmaz, Volkan; Aksoy, Dürdane; Yılmaz, Mustafa; Eser, Enes; Erbas, Oytun
Abstract : Objectives: Critical illness neuropathy (CIN) is a condition that may occur in diseases with severe systemic response, particularly in sepsis. The aim of this study is to investigate the potential anti-inflammatory and lipid-peroxidation inhibiting activities of lacosamide by measuring tumour necrotizing factor-alpha (TNF-alpha), C-reactive protein (CRP), malondialdehyde (MDA) and white blood cells (WBC) using electroneuromyography (ENMG) in rats with sepsis-induced critical illness neuropathy (SICIN). Methods: Cecal ligation and puncture (CLP) procedure was performed on 39 rats to induce a sepsis model. The study groups were designed as follows: Group 1: normal (nonoperative); Group 2: (sham-operated); Group 3: CLP (untreated group); Group 4: CLP and lacosamide 20 mg/kg; Group 5: CLP and lacosamide 40 mg/kg. TNF-alpha, C reactive protein, MDA and WBC levels was measured and compound muscle action potential (CMAP) distal latans, amplitudes were measured by using ENMG in rats with SICIN. Results: When untreated sepsis group was compared with both control and sham groups, CMAP amplitudes and latans were significantly lower ( P < 000.1). When CLP, CLP+lacosamide 20 mg/kg and CLP+lacosamide 40 mg/kg groups were compared, plasma levels of TNF-alpha and MDA were significantly higher in the untreated CLP group ( F = 12.74, P < 0.0001), ( F = 19.43, P < 0.05). In the CLP+lacosamide 40 mg/kg group, CRP levels were significantly lower only compared to the CLP group ( P < 0.001). Discussion: We have showed that lacosamide may have beneficial effects on early SICIN by its potential anti-inflammatory and lipid peroxidation inhibiting activities; however, further comprehensive studies are required to clarify these effects.